MODERATION OF RELIGION AND STRENGTHENING OF DEMOCRACY (Islamic Moderation Values and Its Implementation in Pancasila Democracy) - Andika Ronggo Gumuruh; Faza Amrullah (MAN Insan Cendekia Jambi, 2021)
Indonesia is a very diverse country, there are many ethnic groups, religions and races in it. The process of achieving Indonesian independence was not easy, many lives had to be lost to get that independence. In the BPUPKI session it was agreed that the ideology of the Indonesian nation was Pancasila, where Pancasila itself was initiated by the first President of Indonesia, namely Ir. Sukarno. Pancasila itself contains many things that are very important in the foundation of a country. Pancasila as the way of life of the Indonesian people has a function as a guide or reference for Indonesian people in attitude and behavior, relating to the value system, about good and bad, about fair and unjust, honest and lying, and so on. Pancasila in the Indonesian state is not only the basis of the Indonesian state but also has a position as the national ideology of the Indonesian state. In the ideology used by a nation, there are many values ​​that are good, noble and considered beneficial for the country both for the present and the present. In Indonesia, there are currently six religions that are recognized for their existence, namely Islam, Catholic Christianity, Protestant Christianity, Hinduism, Buddhism and Confucianism (only recognized in the era of President Abdurrahman Wahid).